2003
DOI: 10.1021/la035425o
|View full text |Cite
|
Sign up to set email alerts
|

Binding the Tobacco Mosaic Virus to Inorganic Surfaces

Abstract: We studied the adsorption behavior and surface chemistry of the tobacco mosaic virus (TMV) on well-defined metal and insulator surfaces. TMV serves as a tubular supramolecular model system with precisely known surface termination. We show that if the surface chemistry of the substrate and the pH-dependent chemistry of the molecular surface match, for example, by hydrogen bonding, a strong adsorption occurs, and lateral movement is impeded. Due to the immobilization, the virion can be imaged by atomic force mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 43 publications
6
108
2
Order By: Relevance
“…The measured height of Pt-TMV2cys from the section analysis is approximately 12 nm, which is similar to the apparent height of wt TMV on a gold[111] substrate. 36 …”
Section: Resultsmentioning
confidence: 99%
“…The measured height of Pt-TMV2cys from the section analysis is approximately 12 nm, which is similar to the apparent height of wt TMV on a gold[111] substrate. 36 …”
Section: Resultsmentioning
confidence: 99%
“…AFM experiments showed that it is possible to image TMV at solid-air and solid-liquid interfaces on welldefined substrates such as mica and Au (111). 333 M13 Bacteriophage. Another example of the use of viruses for the assembly of inorganic materials has been given by Belcher and co-workers.…”
Section: Rod-shaped Virusesmentioning
confidence: 99%
“…Second, the TMV is an extensively studied virus by different techniques, and hence its structure, mass and mechanical properties are well-established. TMV is rod-shaped and is formed from approximately 2130 identical protein subunits wound in a 300-nm long helix with a diameter of 18 nm [16][17] . A central hollow cylindrical core holds the viral genome-a 6395-nucleotide strand of RNA.…”
mentioning
confidence: 99%